Adsorptive removal of methylene blue from aqueous solutions by porous boron carbide: isotherm, kinetic and thermodynamic studies - Ugraskan, Volkan; Isik, Birol; Yazici, Ozlem (TAYLOR & FRANCIS INC, 2022)
In this study, the performance of boron carbide (B4C) on the adsorptive removal of methylene blue from aqueous solutions was investigated. Adsorption studies were carried out using different adsorbent dosage, dye concentration, pH, and temperature parameters. The BET analysis results showed the B4C surface area is 317.6 m(2)/g and B4C has a mesoporous structure. From the adsorption studies, the maximum dye removal percentage was obtained as 97.3% at 55 degrees C. Besides, different isotherm models were used during adsorption and the order was determined as Langmuir > Flory - Huggins > D - R > Freundlich > Harkins - Jura. For the Langmuir isotherm, q(m) was calculated as 188.68 mg/g at 55 degrees C. D-R isotherm, enthalpy, and activation energy data showed that adsorption took place physically. The kinetic studies showed that the adsorption was compatible with the pseudo-second-order kinetic model. Besides, it was determined from the thermodynamic studies that adsorption occurs endothermically and spontaneously.
Keywords: Boron carbide; adsorption; methylene blue; isotherms; kinetics; thermodynamics; LOW-COST ADSORBENT; NITRIDE NANOSHEETS; ACTIVATED CARBON; ENHANCED ADSORPTION; EFFICIENT REMOVAL; MALACHITE GREEN; DYE; WASTE; EQUILIBRIUM; POWDER; Engineering